Proteome data to explore the axolotl limb regeneration capacity at neotenic and metamorphic stages - Demircan, Turan; Sibai, Mustafa; Altuntaş, Ebru (Elsevier, 2020)
The presented data article reports protein expression profiles during a time course of limb regeneration in the highly regenerative neotenic and regeneration-deficient metamorphic axolotl (Ambystoma mexicanum). A protein database was first generated from transcriptome data, which was used concomitantly with nanoLC-MS/MS to identify and assess significant changes of protein levels among 0, 1, 4, and 7 days post-amputation (dpa) in both animal stages, yielding a total of 714 significant differentially expressed proteins. Gene ontology categories of these identified proteins were examined in terms of biological processes, molecular function and cellular components. Innate clustering patterns of the samples were investigated using hierarchical clustering and were visualized on a heatmap. The data reported here constitutes an extension of "Comparison of protein expression profile of limb regeneration between neotenic and metamorphic axolotl" article Sibai et al., 2019 [1]. The associated mass spectrometry raw data have been deposited in the ProteomeXchange Consortium (http://proteomecentral.proteomexchange.org) with the dataset identifier PXD014806.
Keywords: Axolotl; Regeneration; Proteomics; LC-MS/MS; Metamorphosis